2020
DOI: 10.1177/2055668320968482
|View full text |Cite
|
Sign up to set email alerts
|

Exploring interface design to support caregivers’ needs and feelings of trust in online content

Abstract: Introduction Family caregivers of people living with dementia require a range of accurate, current, and reliable information throughout the care trajectory. Much of this information is available online, however it can be difficult for caregivers to identify and decide what content is relevant to them. Little is known about how online design cues impact family caregivers’ decision to assess how trustworthy information is and whether to engage with it. Methods Our exploratory research focused on the interface de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 68 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…Of particular relevance to this study, Cyr (2008) reported findings showing that a well-designed website in terms of its navigation elements can lead to high levels of trust and satisfaction with the website. Interface design was also found to support consumers' feelings of trust in online content (Hussein et al, 2020). These results suggest that there is an association between perceived navigation design of the website and the level of trust in the website.…”
Section: Navigation Design (Nd)mentioning
confidence: 68%
See 3 more Smart Citations
“…Of particular relevance to this study, Cyr (2008) reported findings showing that a well-designed website in terms of its navigation elements can lead to high levels of trust and satisfaction with the website. Interface design was also found to support consumers' feelings of trust in online content (Hussein et al, 2020). These results suggest that there is an association between perceived navigation design of the website and the level of trust in the website.…”
Section: Navigation Design (Nd)mentioning
confidence: 68%
“…As previously mentioned, many studies have determined the factors increasing consumers' trust in e-commerce (Amaro & Duarte, 2015;Fimberg & Sousa, 2020;Hong, 2015;Hussein et al, 2020;Lü et al, 2016;Ponte et al, 2015). What seems to be lacking in the literature, however, is a clear explanation of how e-trust can be influenced by website navigation design (Hussein et al, 2020). This study, therefore, attempts to extend previous research by proposing a relationship between navigation issues of the website and e-trust formed in consumers' minds while interacting with a website.…”
Section: Navigation Design (Nd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Apps should have an intuitive and user-friendly interface, making it easy for parents, caregivers, or professionals to navigate and use without extensive training. A simple interface ensures accessibility for a broad user base [ 39 ].…”
Section: Reviewmentioning
confidence: 99%